DOI: 10.11606/d.11.2018.tde-20181127-160501
|View full text |Cite
|
Sign up to set email alerts
|

Planejamento de empresas rurais em Santa Catarina

Abstract: Ti:~C nCllóg:i.co CHPq, d :i. ~:; t :i. n to';;; d i:~ r :. : .). In suport2 financEiro E possibilitaram condiç52s dE rEalizaçio a ProfEssora Dr! Zilda PaEs d2 Barros Mattos, pela eficiente orientaçio proporcionada durante a realizaçio aos Prof2ssqr2s Josd FErrEira dE Noronha PEla o'", :i. i:~ fi t :•:t(;: :~~o no :i. n i c :i. o do c U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
6

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
0
0
6
Order By: Relevance
“…The glyphosate was the pesticide most commonly used, which is in agreement with other authors who also demonstrated that this product is largely consumed in Brazil (Pignati et al 2017) and in North Caroline agent of multiple myeloma in farmers (De Roos et al 2005). Furthermore, this herbicide may be harmful to the farmer and his family's health and may cause fetal malformations (Duke & Powles 2008), hormonal deregulation (Cattani et al 2014, Mesnage et al 2015, liver and kidney problems (Zhu et al 2012, Mesnage et al 2017, tumors and cancer (Greim et al 2015, Hort 2016, CIT/SC 2019.…”
Section: Discussionsupporting
confidence: 71%
“…The glyphosate was the pesticide most commonly used, which is in agreement with other authors who also demonstrated that this product is largely consumed in Brazil (Pignati et al 2017) and in North Caroline agent of multiple myeloma in farmers (De Roos et al 2005). Furthermore, this herbicide may be harmful to the farmer and his family's health and may cause fetal malformations (Duke & Powles 2008), hormonal deregulation (Cattani et al 2014, Mesnage et al 2015, liver and kidney problems (Zhu et al 2012, Mesnage et al 2017, tumors and cancer (Greim et al 2015, Hort 2016, CIT/SC 2019.…”
Section: Discussionsupporting
confidence: 71%
“…A Serra Geral é composta por escarpas que apresentam desníveis de mais de 1.000 m desde sua base até o topo; isso ocorre devido ao empilhamento de várias camadas de rochas sedimentares de diferentes formações geológicas, mais os derrames de efusivas no topo (LUIZ, 2016, p. 103). Na parte que abrange a Depressão da Zona Carbonífera, com cotas altimétricas menores que a Serra Geral e Serra do Leste Catarinense, as paisagens são compostas por morros, colinas, vales e planícies (SANTA CATARINA, 2009). Em relação aos recursos hídricos, nos limites do PNSJ existem diversas nascentes de importantes afluentes das bacias hidrográficas do rio Tubarão e do rio Canoas, além da nascente do rio Pelotas (FERREIRA et al, 2018).…”
Section: Materiais E Métodosunclassified
“…Segundo GAPLAN (1986) os rios da vertente Atlântica em Santa Catarina apresentam um perfil longitudinal bastante acidentado no curso superior. No curso inferior onde cortam as planícies aluviais, geralmente formam meandros, os perfis assinalam baixa declividade.…”
Section: Hipsometriaunclassified